2023
DOI: 10.1097/md.0000000000033020
|View full text |Cite
|
Sign up to set email alerts
|

Single axillary incision endoscopic surgery and liposuction for gynecomastia

Abstract: Gynecomastia is a common type of breast tissue hypertrophy in men. Surgical excision is the most effective treatment for this condition. Minimally invasive surgical techniques can be used to avoid visible chest scarring. In this study, we evaluated the efficacy and safety of single-axillary-incision endoscopic mastectomy and liposuction for the treatment of gynecomastia. Nipplesparing mastectomy via a single-port axillary incision was successfully performed in all patients. Twenty-four bilateral procedures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Varlet et al performed endoscopic subcutaneous mastectomy with 3 ports and in their study, the mean operation time was found to be 93 minutes for each breast. 13 Tukenmez et al 19 performed endoscopic mastectomy from a single axillary incision for 30 gynecomastia patients and they reported 120 minutes of median operation time. The technique we described does not use a port or continuous insufflation, and as a consequence problems and difficulties of endoscopic surgery wouldn't occur.…”
Section: Discussionmentioning
confidence: 99%
“…Varlet et al performed endoscopic subcutaneous mastectomy with 3 ports and in their study, the mean operation time was found to be 93 minutes for each breast. 13 Tukenmez et al 19 performed endoscopic mastectomy from a single axillary incision for 30 gynecomastia patients and they reported 120 minutes of median operation time. The technique we described does not use a port or continuous insufflation, and as a consequence problems and difficulties of endoscopic surgery wouldn't occur.…”
Section: Discussionmentioning
confidence: 99%